Factors associated with professional satisfaction in primary care: Results from EUprimecare project. (2nd October 2017) - Sanchez-Piedra, Carlos Alberto; Jaruseviciene, Lina; Prado-Galbarro, Francisco Javier; Liseckiene, Ida; Sánchez-Alonso, Fernando; García-Pérez, Sonia; Sarria Santamera, Antonio
Abstract: Background: Given the importance of primary care to healthcare systems and population health, it seems crucial to identify factors that contribute to the quality of primary care. Professional satisfaction has been linked with quality of primary care. Physician dissatisfaction is considered a risk factor for burnout and leaving medicine. Objectives: This study explored factors associated with professional satisfaction in seven European countries. Methods: A survey was conducted among primary care physicians. Estonia, Finland, Germany and Hungary used a web-based survey, Italy and Lithuania a telephone survey, and Spain face to face interviews. Sociodemographic information (age, sex), professional experience and qualifications (years since graduation, years of experience in general practice), organizational variables related to primary care systems and satisfaction were included in the final version of the questionnaire. A logistic regression analysis was performed to assess the factors associated with satisfaction among physicians. Results: A total of 1331 primary care physicians working in primary care services responded to the survey. More than half of the participants were satisfied with their work in primary care services (68.6%). We found significant associations between satisfaction and years of experience (OR = 1.01), integrated network of primary care centres (OR = 2.8), patients having direct access to specialists (OR = 1.3) and professionals having access to data on patient satisfaction (OR = 1.3). Public practice, rather than private practice, was associated with lower primary care professional satisfaction (OR = 0.8). Conclusion: Elements related to the structure of primary care are associated with professional satisfaction. At the individual level, years of experience seems to be associated with higher professional satisfaction.